Assessment of parametrial invasion of cervical carcinoma, the role of T2-weighted MRI and diffusion weighted imaging with or without fusion. Issue 10 (October 2019) - Mongula, J.E.; Bakers, F.C.H.; Mihl, C.; van Gorp, T.; Kruitwagen, R.F.P.M.; Slangen, B.F.M.
Abstract : AIM: To evaluate the diagnostic performance of diffusion-weighted imaging (DWI), with and without fusion images, in addition to regular T2-weighted (T2W) sequences for assessment of parametrial invasion. MATERIALS AND METHODS: This prospective cohort included cervical cancer patients who underwent preoperative magnetic resonance imaging (MRI) with T2W and axial DWI sequences prior to radical hysterectomy. Retrospectively, two radiologists independently and blindly scored the likelihood of parametrial invasion by means of a six-point confidence scale. Parametrial invasion was determined by surgical–pathological results. Performance indices for diagnostic tests and area under the receiver operating characteristic curve (AUC) analyses were performed. P- Values of <0.05 were considered statistical significant. Ethical board approval was obtained. RESULTS: Of 65 included patients, parametrial invasion was found in eight patients. A statistically significant increase in diagnostic performance for the assessment of parametrial invasion was found when T2W MRI was fused with DWI (fusion T2W/DWI), especially decreasing false-positive findings: the positive predictive value of parametrial invasion using T2W MRI versus fusion T2W MRI/DWI increased from 29% to 50% for observer 1 and from 23% to 50% for observer 2 (AUC=0.80–0.67 versus 0.94–0.94). CONCLUSIONS: Fusion T2W MRI/DWI shows a significant increase in diagnostic performance for the assessment of parametrial invasion in early-stage cervical carcinoma. Highlights: Fusion T2W/DWI is superior for assessing parametrial invasion in cervical cancer. False positive findings of parametrial invasion decreased with fusion T2W/DWI. Fusion T2W/DWI could improve staging and sequential allocation to the correct treatment strategy.